Identification of the most common problems in functioning of individuals with spinal cord injury using the international classification of functioning, disability and health - I. Kirchberger (2018)
Study design: Cross-sectional, multicenter study. Objectives: To identify the most common problems of individuals with spinal cord injury (SCI) in the early post-acute and the long-term context, respectively, using the International Classification of Functioning, Disability and Health (ICF) as a frame of reference. Setting: International. Methods: The functional problems of individuals with SCI were recorded using the 264 ICF categories on the second level of the classification. Prevalence of impairment was reported along with their 95% confidence intervals. Data were stratified by context. Results: Sixteen study centers in 14 countries collected data of 489 individuals with SCI in the early post-acute context and 559 in the long-term context, respectively. Impairments in thirteen ICF categories assigned to Body functions and Body structures were more frequently reported in the long-term context, whereas limitations/restrictions in 34 ICF categories assigned to Activities and Participation were more frequently found in the early post-acute context. Eleven ICF categories from the component Environmental Factors were more frequently regarded as barriers, facilitators or both by individuals with SCI in the early post-acute context as compared with individuals with SCI in the long-term context. Only two environmental factors were more relevant for people with SCI in the long-term context than in the early post-acute context. Conclusion: The study identified a large variety of functional problems reflecting the complexity of SCI and indicated differences between the two contexts. The ICF has potential to provide a comprehensive framework for the description of functional health in individuals with SCI worldwide. © 2010 International Spinal Cord Society All rights reserved.